2017
DOI: 10.1111/mmi.13736
|View full text |Cite
|
Sign up to set email alerts
|

Covalent attachment and Pro‐Pro endopeptidase (PPEP‐1)‐mediated release of Clostridium difficile cell surface proteins involved in adhesion

Abstract: In the past decade, Clostridium difficile has emerged as an important gut pathogen. This anaerobic, Gram-positive bacterium is the main cause of infectious nosocomial diarrhea. Whereas much is known about the mechanism through which the C. difficile toxins cause diarrhea, relatively little is known about the dynamics of adhesion and motility, which is mediated by cell surface proteins. This review will discuss the recent advances in our understanding of the sortase-mediated covalent attachment of cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…CD2831 and another c-di-GMP controlled putative adhesin, CD3246, are recognized and cleaved by ZmpI/PPEP-1. Consistently, it was demonstrated that at low c-di-GMP levels, ZmpI/PPEP-1 is produced and cleaves the low amount of CD2831 and CD3246 present, thus limiting bacterial adhesion to the host 4446 .…”
Section: Introductionmentioning
confidence: 68%
“…CD2831 and another c-di-GMP controlled putative adhesin, CD3246, are recognized and cleaved by ZmpI/PPEP-1. Consistently, it was demonstrated that at low c-di-GMP levels, ZmpI/PPEP-1 is produced and cleaves the low amount of CD2831 and CD3246 present, thus limiting bacterial adhesion to the host 4446 .…”
Section: Introductionmentioning
confidence: 68%
“…The zmpI mRNA (CD630_28300) contains a class I riboswitch and is negatively regulated by c-di-GMP. The opposing regulation of ZmpI and its surface protein targets has been proposed to integrate increased c-di-GMP to simultaneously promote production of the surface proteins and inhibit their release by ZmpI [36]. Together these studies indicate that, as in other bacterial species, C .…”
Section: How Does C-di-gmp Signaling Through Riboswitches Impact Pathmentioning
confidence: 99%
“…The gene encoding PPEP-1 in C. difficile (ppep-1/cd2830) is found adjacent to cd2831, the gene that encodes its substrate (21,22). In CD2831, multiple PPEP-1 cleavage sites are present, located just above the site of attachment to the peptidoglycan layer.…”
Section: Ppep-1 Homologs Are Found In Paenibacillus Speciesmentioning
confidence: 99%
“…We have recently characterized a novel secreted protease in Clostridium difficile, Pro-Pro endopeptidase (PPEP 3 -1, 3.4.24.89, previously known as Zmp1 (19) (MER0494994)), which has a remarkable preference for hydrolyzing a Pro-Pro bond (20,21). PPEP-1 cleaves two cell C. difficile surface adhesion proteins (CD2831 and CD3246) and as such is thought to play a role in switching from an adhesive to a motile phenotype (22). The two substrates of PPEP-1 contain multiple consecutive cleavage sites (in total 13), and a consensus motif analysis showed that in addition to the prolines surrounding the scissile bond, highly conserved residues are found, and cleavage preferentially occurs at sites that are composed of (VLI)NPPVP (P3-P3Ј).…”
mentioning
confidence: 99%